Assessment of Anti-Mullerian Hormone and Anti Ovarian Antibody in the Sera of Patients with Polycystic Ovarian Syndrome in AL-Najaf Al-Ashraf Province (Medico Legal Update, 2020)
Polycystic ovarian syndrome(PCOS)is the most common endocrinopathy,that affects 5 to 20% of women in age of(12-45year)and cause a widespread of reproductive disorder in women and it is a major cause of hirsutism,acne,hormonal disturbance and infertility. Women with PCOS may associated with health conditions obesity,amenorrhea, oligomenorrhea,hyperandrogenemia and insulin resistance.The PCOS patients are with increased risk for type 2diabetes mellitus,diabetic complications,dyslipidemia and cardiovascular disease .Objective: Aim of the study to investigate the pathogenicity,disease severity and early diagnosis roles anti-Mullerian hormone and anti-ovarian antibody in ladies with PCOS.Conclusion: Polycystic ovarian syndrome was related to the increase level of AMH in different age of PCOS patients,which comprised 55.0% in PCOS patients that cause defect in ovulation and resulting fertility problem,while no relationship between anti-ovarian antibody and patients with PCOS.